(untitled) (Journal of Contemporary Issues in Accounting, 2024)
This paper investigated the relationship between State Governments’ revenue streams and the economic recovery in Nigerian during the period1990 -2023. Economic recovery involves the revitalization of a national economy following a period of downturn or recession. The study employed ex-post facto research design, the area of study is Nigeria, secondary data was used and obtained from statistical bulletin for various years. Other relevant data was used. Data were analyzed with descriptive and inferential statistics at 5% level of significance. The findings of the study showed that. States Governments’ allocation from the federation account has a significant positive effect on nominal gross domestic product in Nigeria (p-value = 0.0116). State governments’ Internally generated revenue has insignificant positive effect on nominal gross domestic product in Nigeria (p-value = 0.0782). State governments’ share of the Value added tax has insignificant positive effect on nominal gross domestic product in Nigeria (p-value = 0.0903). The study recommended that State governments should improve strategies to increase internally generated revenue through more effective collection of taxes, fees, and other levied sources. Expanding the tax net and minimizing evasion can boost this important revenue stream to support further economic growth.